IMPACT DE COMMERCIALISATION ET DISTRIBUTION URBAINE DES VIVRES FRAIS SUR L’EQUILIBRE FINANCIER D’UNE CHAMBRE FROIDE, CAS DE CONSTRUCTION METALLIQUE ET NAVALE(COMENAV) A KISANGANI - Salumu, Fiston WANDJA (IJRDO - Journal of Social Science and Humanities Research, 2023)
Hunger, dependant on poverty, continues to worry the populations of subtropical countries on a daily basis.The marketing of fresh food on the market is not only about the flow but and above all about the way in which the company expects to achieve the profitability of its commercial activity. In the distribution chain are intercalated other factors that influence the determination of cost prices without forgetting the sale force of the other one competitors supplying either the same or similar products on the hand and the cascading intermediation creating circuits (short,medium and long) and by parcels, retailers, and consequently affects the cost price and erodes the purchasing power of the end consumer.To do this, two distinct and clears situations; the first is said to be very good in 2022, this is explained by the FRN which is higher than the BFR, consequently, the positive cash flow. The second, unhealthy in 2020,2021.